UBUDIAH ACCORDING TO IMAM NAWAWI AL-BANTANI (W.1897 AD) IN THE BOOK OF MARAH LABID LI KASYFI MAKNA OF THE QURAN MAJID. - Muzakkir Muzakkir; Arifinsyah Arifinsyah; Riza Faisal Husaini (Fakultas Ushuluddin dan Studi Islam, 2020)
AbstractThis study aims to describe the Ubudiah according to Imam Nawawi Al-Bantani (W.1897 AD) in the Book of Marah Labid li Kasyfi Makna of the Quran Majid. This type of research is a library research with a qualitative approach. The research method used is the method of interpretation that is tahlily method. The source of this research is the interpretation of Marah Labid li Kasyfi Makna of the Quran Majid, other commentaries and literature relating to ubudiah, while the data analysis technique is done using content analysis. The results of this study are Ubudiah is the servitude of a servant to His Rabb, which is a servant when worshiping Allah Almighty is not merely to get rewards, in order to avoid the fire of hell, but the goal is to worship Allah Almighty in order to get His pleasure . The meaning of ubudiah according to Shaykh Imam Nawawi Al-Bantani in the book of the Marah Labid Li Kasyfi Makna of the Quran Majid is mentioned in his interpretation that a servant is classified into three parts: a. There are servants who worship Allah only because of Allah. is a God worthy of worship, whether he is given favor or not blessed. b. There are servants who worship Allah SWT because they are given Favor by Allah. continously. c. There are servants who worship Allah. because there is fear in him. Ubudiah according to Imam Nawawi al-Bantani has very close relevance in daily life, both in the political, economic, social and tolerance fields